The Portrait of Surau as a Forerunner of Madrasah: The Dynamics of Islamic Institutions in Minangkabau Toward Modernization - Zainal Efendi Hasibuan (AJIS: Academic Journal of Islamic Studies, 2016)
Surau as traditional educational institutions in Minangkabau, West Sumatera province, has significantly contributed to the emergence of outstanding figures or muslim scholars in Indonesia, some of them are those who have international reputation, such as Buya Hamka, Muhammad Natsir, Muhammad Hatta, and Haji Agus Salim. As the most influenting scholar among Indonesian muslim scholars, Sheikh Ahmad Khatib al-Minangkabawiy was used to be the teacher of the two founders of two major organizations in Indonesia, namely KH. Ahmad Dahlan the founder of Muhammadiyah and KH. Hashim Asy'ariy the founder of Nahdatul Ulama. On the other hand, the return of Kaum Muda Minangkabau (the youth of Minangkabau) had a strong effect on the development and performance of Surau as an educational institution. The function of Surau has developed, not only as a place for Islamic observance but also a centre of learning and teaching activities. The paper will discuss about the phases of the modernization of surau to be madrasah. This study is a library research that used content analysis. It is found that the changing function of surau from place of worship to be madrasah (Islamic school) was led by the modernist that returned after finishing studying from Mecca, they were called the youth. The changing of surau had an impact on the education system, such as aspects of the curriculum, teaching methods, teachers, students, management, and other educational components. Modernization does not only apply to aspects of the changing system but also the name. Some surau were renamed after changing into madrasah and pesantren (Islamic boarding school), such as Jembatan Besi Surau which became Sumatra Thawalib Madrasah of Padang Panjang, Alin Tagak Surau which became Alin Tagak Islamic Boarding School of West Pasaman. Keywords: surau, madrasah, Minangkabau, Modernization